PERSEPSI AKUNTAN DAN MAHASISWA AKUNTANSI TERHADAP KEMAMPUAN YANG HARUS DIMILIKI OLEH SEORANG FORENSIC ACCOUNTANT - Eman Sukanto; Widaryanti Widaryanti (STIE Pelita Nusantara Semarang, 2019)
This study aims to analyze differences in perceptions of Government Auditors, Public Accountants, Corporate Internal Auditors, Corporate Accountants, Accounting Lecturers and Senior Accounting Students for the capabilities that must be possessed by Forensic Accountants. The object of this research is the professional group of Government Auditors, internal government Auditors, Public Accountants, Corporate Internal Auditors, Corporate Accountants, Accounting Lecturers and Senior Accounting Students in the Jakarta and Central Java regions. This study uses a purposive sampling technique in data collection. Data was obtained by distributing questionnaires to each group. A total of 156 questionnaires were collected. Government auditor samples were distributed to Central BPK employees and inspectors in Central Java, Public Accountants, Internal Auditors, Corporate Accountants in several large companies in Jakarta and Central Java. While the questionnaire for lecturers and senior students was distributed to PTN and PTS in Jakarta and Central Java. Data analysis was carried out with One Way Analysis of Variance (Annova). The results showed that there is no difference in perception between government auditors and internal government, public accountants, corporate accountants, company internal auditors, accounting lecturers and accounting students about the capabilities that must be possessed by forensic accountants. There are differences in perceptions between government internal auditors, public accountants, corporate internal audits and accounting lecturers with senior accounting students about the capabilities that must be possessed by forensic accountants. There is no difference in perception between government auditors and company accountants with senior accounting students about the capabilities that must be possessed by forensic accountants. In addition, overall respondents gave a high assessment of the knowledge, traits, skills and abilities that Forensic Accountants must possess. This shows that the respondent agrees that a forensic accountant needs to have high abilities according to the AICPA FVS Section criteria.